Tunnel face stability analysis using Kinematical Element Method. (March 2019) - Qarmout, Mahmoud; König, Diethard; Gussmann, Peter; Thewes, Markus; Schanz, Tom
Abstract: This paper introduces a new approach to investigate the tunnel face stability. In the proposed approach a 3D KEM (Kinematical Element Method) model is developed which consists of two rigid blocks, tetrahedron wedge block (lower part) and triangular prism block (upper part). In order to incorporate the influence of the 3D soil arching in silo for predicting the minimum support pressure, it is presumed a 3D active earth pressure acting on the vertical prism's slip surfaces from the adjoining soil. The results given by the KEM model are compared with the results of numerical simulations, analytical approaches, and physical model tests available in literature. Similar to Terzaghi's superposition method commonly used in bearing capacity analysis, the minimum support pressure is expressed by summation of cohesion (c), surcharge load (q) and unit weight of the soil ( γ ) multiplied by non-dimensional bearing capacity coefficients N c, N q and N γ . Simple formulas have been developed to compute the non-dimensional coefficients. The N γ, N c, and N q formulas are presented as function of internal friction angle ( φ ), and cover depth to tunnel diameter ratio (C/D). The proposed KEM model for the tunnel face stability gives good results in term of minimum support pressure compared to physical model test results, various analytical and numerical solutions for the tunnel face stability analysis of shallow tunnels.